2012
DOI: 10.5505/abantmedj.2012.09797
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly cartilage graft myringoplasty results

Abstract: Bu çalışmanın amacı Kulak Burun Boğaz Kliniğine başvuran ve "kıkırdak greft butterfly miringoplasti" ameliyatı yaptığımız kronik otitis medialı hastalarda işitme düzeyini retrospektif olarak analiz etmektir. Yöntemler: Çalışmaya 22 hasta (26 kulak) dahil edildi. 18 hastada genel anestezi altında 8 hastada lokal anestezi altında, gerçekleştirildi. Cerrahi 22 hastada tek kulakta 4 hastada her ki kulakta ve Eavey tarafından tarif edildiği şekilde gerçekleştirildi. Ameliyat öncesi ve ameliyat sonrası yapılan odyol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Similarly, other studies done by Kim et al17 , Eren et al18 , Yu et al19 , Apuhan et al20 and Shrestha et al21 also had reported significant hearing improvement observed after butterfly cartilage myringoplasty. But these studies showed the graft uptake of butterfly cartilage and lack the comparison with temporalis fascia.…”
supporting
confidence: 60%
“…Similarly, other studies done by Kim et al17 , Eren et al18 , Yu et al19 , Apuhan et al20 and Shrestha et al21 also had reported significant hearing improvement observed after butterfly cartilage myringoplasty. But these studies showed the graft uptake of butterfly cartilage and lack the comparison with temporalis fascia.…”
supporting
confidence: 60%